An experimental demonstration of quantum NOT gate: transition from classical to quantum regime - Sajeed, Shihan; Haider, A F M Yusuf (© 2010 IEEE, 2017)
This conference paper was presented in the 2010 IEEE International Conference on Electro/Information Technology, EIT2010; Normal, IL; United States; 20 May 2010 through 22 May 2010; Category numberCFP10EIT-ART; Code 82572 [© 2010 IEEE] The conference paper's definite version is available at: 10.1109/EIT.2010.5612122